Successful pregnancies and reduced treatment requirement while breast feeding in a patient with congenital hypoparathyroidism due to homozygous c.68C>A null parathyroid hormone gene mutation. (26th May 2018) - Dixon, Joanne; Miller, Steven
Abstract : A female patient with consanguineous parents presented at the age of 4 with isolated hypoparathyroidism due to a parathyroid hormone (PTH) gene mutation. She was managed with alfacalcidol and calcium supplements, and developed normally. Her consanguineous parents described symptoms suggestive of hypocalcaemia but had normal serum calcium and low normal PTH levels. A molecular diagnosis obtained in her adulthood revealed the presence of homozygous point mutation (c.68C>A) in exon 2 introducing a premature stop codon resulting in a non-functional precursor protein. This mutation has been reported only once before. Our patient remained on stable doses of alfacalcidol during pregnancy, but stopped all supplementation while breast feeding. This case confirms that alternative mechanisms (likely breast-derived parathyroid hormone-related protein) contribute to calcium homeostasis during breast feeding. Heterozygotes for the c.68C>A mutation may have latent hypoparathyroidism and maintain calcium homeostasis except during prolonged hypocalcaemia. This would suggest incomplete dominance, or a dose effect of the wild-type PTH allele.